Does common channel length affect surgical choice in female congenital adrenal hyperplasia patients? - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (ELSEVIER SCI LTD, 2014)
Objective: Partial/total urogenital sinus mobilization (UGSM) is one of the recommended techniques for treatment of female congenital adrenal hyperplasia (CAH). In this study we compared the length of common channel (CC) and type of operation performed in CAH patients. Patients and methods: We retrospectively analyzed data of patients receiving surgery for female CAH. Patients were separated into three groups: group 1 had partial UGSM, group 2 had total UGSM, and group 3 had total UGSM plus the vaginal anterior wall was made from CC. Age at surgery, length of CC, surgical time, follow-up time, and complications were compared. Results: There were a total of 29 patients. For groups 1, 2, and 3, the average age at surgery was 47.2 months, 14.4 months, and 21.3 months, respectively, and the average CC length was 1.25 cm, 3.1 cm, 4.3 cm, respectively. The average time of surgery was 165 min, 193.1 min, 282.5 min, respectively. The average follow-up time was 34.7 months, 36.3 months, 28.3 months, respectively. There were two complications (UGS flap necrosis and opening of sutures) in the third group. Conclusion: We advise the use of partial UGSM for CC of 0.5-2 cm, total UGSM for CC of 2.5-3.5 cm, and total USM with use of CC as the anterior vaginal wall in CC >= 4 cm in length. Good cosmetic and functional results are obtained with this approach. (C) 2014 Journal of Pediatric Urology Company. Published by Elsevier Ltd. All rights reserved.
Keywords: Congenital adrenal hyperplasia; Urogenital sinus mobilization; Common channel; UROGENITAL SINUS MOBILIZATION; FEMINIZING GENITOPLASTY; AMBIGUOUS GENITALIA; URINARY CONTINENCE; SEX DEVELOPMENT; SURGERY; REPAIR; DISORDERS; ANOMALIES; INTERSEX